2020
DOI: 10.22271/chemi.2020.v8.i5k.10391
|View full text |Cite
|
Sign up to set email alerts
|

Study on gene action involved in inheritance of yield and its contributing traits in brinjal (Solanum melongena L.)

Abstract: The present investigation was carried out to evaluate the 45 F1 hybrids derived from half diallel fashion along with ten parents in randomized block design with three replications during Rabi season of 2018-19 (E1) and 2019-20 (E2) at the Main Experiment Station (MES) of the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
1
1
0
Order By: Relevance
“…According toMather (1974), a population undergoing continuous directional selection develops complementary epistasis. Our reports are in acceptance with the reports ofGopinath and Madalageri (1986),Chadha and Hegde (1987),Singh and Rai (1990),Lawande et al (1992),Kathiria et al (1998),Vaghasiya et al (2000),Kumar et al (2004), andGunasekar et al (2018) who also reported the significant additive gene effects and additive  additive interaction gene effects for fruit length, fruit diameter and fruit weight of brinjal, andChadha and Sharma (1991) reported duplicate epistasis for fruit weight and fruit number per plant. The results of our experiments also exhibited both positive and negative values for degree of dominance: positive values of 0.48 and 1.61 were observed for fruit length and fruit weight, respectively; the negative values of À0.97 and À0.94 were observed…”
supporting
confidence: 91%
“…According toMather (1974), a population undergoing continuous directional selection develops complementary epistasis. Our reports are in acceptance with the reports ofGopinath and Madalageri (1986),Chadha and Hegde (1987),Singh and Rai (1990),Lawande et al (1992),Kathiria et al (1998),Vaghasiya et al (2000),Kumar et al (2004), andGunasekar et al (2018) who also reported the significant additive gene effects and additive  additive interaction gene effects for fruit length, fruit diameter and fruit weight of brinjal, andChadha and Sharma (1991) reported duplicate epistasis for fruit weight and fruit number per plant. The results of our experiments also exhibited both positive and negative values for degree of dominance: positive values of 0.48 and 1.61 were observed for fruit length and fruit weight, respectively; the negative values of À0.97 and À0.94 were observed…”
supporting
confidence: 91%
“…Thus the result clearly indicated superiority of parent BBSR-08-2 to induce vigourness in brinjal which may be used in future brinjal improvement programme. Complementary reports of significant disparity among the F 1 crosses and parents in brinjal for vegetative growth traits were proclaimed earlier by Sivakumar et al [11], Vethamoni and Praneetha [12], Kumar et al [13], Khobragade et al [14] and Tripathy et al [10].…”
Section: Resultsmentioning
confidence: 58%